The short-duration sweetpotato breeding in the Mekong Delta: Observation Trial Report - International Potato Center (2024)
Mekong Delta region has the largest sweetpotato production in Vietnam. In general, sweetpotato is moderately tolerant to salinity and heat and considered as a climate resilient crop. All parts of sweetpotato from vines to roots can be used for multiple purposes such as animal feeding, human consumption, biofuel, and various forms of processing. The global market for sweetpotato is growing, and there is a great potential for the Mekong region to increase sweetpotato production by incorporating it in the rice cropping system as well as utilizing the coastal sandy-soil zone. However, there are some challenges to promote sweetpotato for smallholder farmers in the Mekong Delta region. It takes 4-5 months to harvest sweetpotato, which is too long to incorporate into the rice cropping system. Currently, the rice-sweetpotato rotation is only implemented in some areas in Vinh Long province. Furthermore, there are specific trait preferences for Southeast Asia, such as purple flesh and yellow flesh with high dry matter content, which limit variety options for growers, resulting in the dependency on single sweetpotato variety and its informal seed systems. Third, there is an emerging disease in the region in which major varieties in the Mekong region appear to be susceptible. To address those challenges, International Potato Center (CIP) has initiated a breeding experiment under the CIP sweetpotato Asia short duration breeding pipeline (BP00052). The first batch of true seeds are orange flesh with high dry matter (above 29%). This short-duration genotypes have a great potential to be adopted in the rice cropping system as they can be harvested in 3 months instead of 5 months. It can be for exporting to China or domestic market if the traits meet local demand. True seeds with elite crosses (humid tropics) were sent from San Ramon, Peru to Vietnam in September 2023 and germinated at Potato, Vegetable, Flower Research Institute (PVFC) in Da Lat, Lam Dong Province, Central Highlands of Vietnam where the temperature is stable year around. The observation yield trial (OT) was conducted with 1324 genotypes from 9 families in the campus of the Cuu Long Rice Research Institute from late January to late April (90 days). The cuttings were sent from PVFC. Two checks were selected from locally available varieties for a comparison purpose: one is Khoai Lang Mat from Central Highlands which is Vietnam’s only commercial orange flesh variety. Another one is Khoai Sua, a white flesh local variety grown in the Mekong Delta region of Vietnam. The selection of genotypes for the next advanced trial was made based on the following steps: step 1: the number of marketable roots equal to or above 1.7; step 2: Vine vigor - score 2 or 3; step 3: Remarks about diseases (discarding all with the comment on diseases); step 4: the number of damaged roots by weevils, nematodes and/or pathogens; step 5: the number of marketable roots above 2.0 or above; step 6: high dry matter content (above 28%); step 7: disease damage 1 or above; and step 8: the number of marketable roots equal to or above 2.3. Step 9: the number of vines in their mother plants in Dalat equal or larger than five. Overall, 167 genotypes (10.7% of the total genotypes) were selected in consultation with partners and the next experiment will be planned starting in July to August when new planting materials and experiment fields are ready. This report outline the process and result of the observation trial, as well as other relevant activities such as stakeholder consultation and a household survey.